Kinerja Pegawai Pelayanan Gawat Darurat Rumah Sakit Umum Daerah Teluk Kuantan Kabupaten Kuantan Singingi - Pangendra, Dio; Tua, Harapan (Lembaga Pengkajian Dan Pengembangan Sumberdaya Pembangunan (lppsp), 2023)
The goal of health development applies to all hospitals in Indonesia, one of whichis the Regional General Hospital. Regional General Hospital is a hospital established and managed by the Regional Government in Law no. 44 of 2009 article 7. At Teluk Kuantan Hospital for emergency services there are still public complaints regarding employee performance that is not in accordance with the Minimum Service Standards, so the hospital received a warning from the local government. So, researchers want to know how the performance of the Employees of the Teluk Kuantan Regional General Hospital for Emergency Services is. The theoretical concept used in this study is an employee performance indicator by Riduwan (2008). The research method used is a qualitative research method with a descriptive approach through interviews and documentation. The results of this study are that the performance of employees at the Emergency Service Regional General Hospital is still not optimal and not in accordance with the Duties and Functions that have been made. The inhibiting factors for performance are the lack of infrastructure, lack of employee skills and lack of human resources.